The The Effectiveness of Gamification on Enhancing Students' Vocabulary Mastery in Reading Descriptive Text - Wardhani, Khairul Mutmainnah Zahratul (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
One alternative learning tool that students can use to enhance their vocabulary mastery in reading is gamification. Yet, not much research has analyzed the implementation of gamification as a teaching media to help students in junior high school expand their vocabulary, particularly when it comes to reading. The primary goal of this research is to find out the differences related to vocabulary mastery improvement of 9th grade students at one junior high school in Indonesia, among those who use gamified learning tools “Genially, Wordwall, Blooket” and those who do not. A quasi-experimental design was employed in the study, with the researcher administering tests to collect data. Moreover, 62 students from one junior high school in Surabaya participated in the research: 31 students from 9B (the experimental class) and 31 students from 9D (the control class). According to the research findings, the significance value obtained is below 0.05, and the eta squared value is 0.406 at a modest level, indicating that the vocabulary learning outcomes of the experimental and control groups varied significantly. In conclusion, gamification substantially enhances students' reading vocabulary knowledge.